2018
DOI: 10.1080/17843286.2018.1511279
|View full text |Cite
|
Sign up to set email alerts
|

Smart diapers for nursing home residents with dementia: a pilot study

Abstract: This study indicates that the sensor detects and notifies wetness but is not sensitive enough for using it as an indicator for diaper change in people with severe dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…To the best of our knowledge, this study is the first to investigate the feasibility of a smart diaper system in an acute care hospital. The only previous study was conducted with 18 people with dementia living in nursing homes and estimated the saturation of diaper capacity indirectly rather than measuring the volume of urine [ 36 ]. The study reported that the saturation errors between the smart diaper system and FVCs were –26% to 39% in the regular diaper (450 mL) with 51 urination records, and –34% to 30% in the super diaper (1000 mL) with 46 records, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to investigate the feasibility of a smart diaper system in an acute care hospital. The only previous study was conducted with 18 people with dementia living in nursing homes and estimated the saturation of diaper capacity indirectly rather than measuring the volume of urine [ 36 ]. The study reported that the saturation errors between the smart diaper system and FVCs were –26% to 39% in the regular diaper (450 mL) with 51 urination records, and –34% to 30% in the super diaper (1000 mL) with 46 records, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, given the high healthcare resource utilization and costs associated with anticholinergic burden, efforts to reduce the levels of anticholinergic burden could result in decreased utilization and costs, specifically among LSNH residents with OAB. Additionally, the use of pads and diapers would avoid contributing to anticholinergic burden in the LSNH population with OAB [11,12]; however, it is unclear whether their use would result in a net reduction economic burden and warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Among residents with dementia and those who are relatively immobile, behavioral strategies may be less successful and the use of pads and diapers may be preferred. Both behavioral strategies and the use of pads and diapers avoid contributing to polypharmacy among patients; however, it may add to the economic burden of the condition [11,12]. OAB pharmacotherapy is primarily comprised of antimuscarinic agents, which are part of the class of oral anticholinergic medications [13]; however, anticholinergics are associated with several central and peripheral adverse effects.…”
Section: Data Sourcementioning
confidence: 99%
“…Wireless Communications and Mobile Computing smartwatch-based communication system for nursing homes [23], which improve communication between residents and caregivers, thus reducing staff response time and improving residents' safety; or an experimental smart diaper [24] as an indicator of saturation for diaper change in people with dementia living in nursing homes. On the other hand, there are rehabilitation assistance projects, such as a new electroinformatics assistive medical system [25] used for the communication with neuromotor disabled patients, which allows bidirectional communication through using an interface with a software application by using different types of sensors including switch-type sensors or eye tracking devices; a system for monitoring and rehabilitation services for elderly [26], based on mobile and wearable technologies ready to be used in residential long-term care facilities to reduce the risk of depression and social isolation; a telecare and telerehabilitation system using computer vision techniques [27]; or a software application for tablet device [3] to support social connections and reducing responsive behaviours of people with dementia while in a care setting, such as nursing homes.…”
Section: Motivationsmentioning
confidence: 99%